Geomembranes : identification and performance testing : report of Technical Committee 103-MGH, Mechanical and Hydraulic Testing of Geomembranes, RILEM, (the International Union of Testing and Research Laboratories for Materials and Structures) /: identification and performance testing : report of Technical Committee 103-MGH, Mechanical and Hydraulic Testing of Geomembranes, RILEM, (the International Union of Testing and Research Laboratories for Materials and Structures). ([2014?]) - Unknown
No abstract available